Ilokusi Direktif dan Implikatur pada Iklan Instagram dalam Bahasa Jepang dan Bahasa Indonesia: Kajian Pragmatik - Heryathan, Abkha; Iriantini, Sri (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 1 (2023), 2023)
In understanding an advertisement, it is necessary to comprehend a pragmatic context. This study discusses directive speech acts and implicatures in advertising on Instagram with a pragmatic study. The purpose of the study was to identify and describe the directive speech acts and their implicatures contained in the Instagram uploads of food products in Japanese and Indonesian and to compare the similarities and differences based on the theory of contrastive analysis. The method used is the descriptive qualitative method. The data source is obtained from the Instagram caption of food products. The results of this study are; (1) directive speech acts and implicatures of Japanese speakers are to; begging, ordering, and suggesting, (2) directive speech acts and implicatures of Indonesian speakers are to ; inviting, ordering, and suggesting, (3) the similarity of advertising is that Japanese speakers and Indonesian speakers tend to use command directive speech acts to convey the meaning of the suggestion, and use request directive speech acts to convey the meaning of the command, the difference in advertising is that Japanese speakers tend to use fantasy promotion strategies about the product, while Indonesian speakers tend to use group life promotion strategies.